Strategies to Improve Employee Engagement and HR Quality at M Educational Institution Jakarta - Xi, Hecan; Sukamdani, Hariyadi B.; Maharani, Maya Dewi Diyah (Jurnal Ilmiah Sumber Daya Manusia, 2024)
The development of education is no less important than the economic and social world. However, in recent years the workforce in the world of education has experienced significant turnover which has hampered the development of teaching. Therefore, it is necessary to analyze and discuss the level of employee engagement and the quality of human resource management using the example of the educational institution M Educational Institution Jakarta. This research was conducted by conducting interviews and distributing questionnaires to educational personnel as subjects. In this study, we identified the core concepts of employee engagement in educational institutions, designed an engagement questionnaire and a satisfaction questionnaire, and conducted a survey. Getting the results from this research, there are problems such as incomplete human resource development mechanism, high human resource mobility, serious exit of high-quality human resources, unbalanced faculty staffing structure, and incomplete performance evaluation and incentive mechanism. Analyzing the problems and their causes, it is necessary to propose constructive solutions and countermeasures, identify common problems in employee participation and human resource management in educational institutions, and improve strategy development and policy adjustment depending on the problems. The result of this research is that increasing employee engagement and the quality of human resources is very important. In the development of the M Educational Jakarta institution, it requires the implementation of a scientific and rational human resource management mechanism, with the concept of project management as a systematic implementation framework, which can also be a guide in managing HR in educational institutions, and ensuring the effectiveness of HR operations.